의과대학 강의실의 좌석 선호도와 학업성취도 관계 분석 - 유효현(Hyo Hyun Yoo); 박지해(Ji Hae Park); 김정수(Jung Su Kim); 김형태(Hyoung Tae Kim); 김영전(Young Jon Kim); 김동찬(Dong (Korean journal of medical education, 2012)
Purpose: This study aimed to explore the relationship between students' seating preferences and academic achievement in medical school. Methods: The subjects of this study were 109 second-year students in C medical school. The pattern of seat selection of 109 students was surveyed by participant observation for 48 days, and a questionnaire was administered to determine the factors that were considered by students. Using SPSS version 12.0, we analyzed the factors that students considered with regard to seat selection and seat preference and the frequency of seat movements between areas. We performed one-way ANOVA to analyze the differences in academic achievement between students who moved seats versus those who did not. Results: The most common reasons for seat selection were to focus better on the lecture (60 students), to focus better on lecture, and to feel familiar with the same seat (60 students). Students' preferred seats were in rows A4, A7, A5, and A3 (in descending order), which are primarily the central sections, and columns B15, B1, B14, B19 (in descending order), which are primarily both ends of the division. The difference in academic achievement between students who moved seats and those who did not was not significant (p>0.05). Among students who did not move seats, the difference in academic achievement between 9 seating areas was not significant in 6 subjects (p>0.05). Conclusion: The results of this study suggest that we should reconsider a professor's general perception regarding academic achievement according to seat location. KCI Citation Count: 6